2015
DOI: 10.1128/aac.00388-15
|View full text |Cite
|
Sign up to set email alerts
|

Nephrotoxicity Comparison of Two Commercially Available Generic Vancomycin Products

Abstract: e To date, no comparative clinical studies have investigated the effects of different vancomycin products on nephrotoxicity. The objective of this single-center, retrospective, matched-cohort study was to investigate the impact of two different vancomycin products on the development of nephrotoxicity. The study population included adults receiving a single vancomycin product, from either Pfizer or Hospira, for their entire course of therapy. Patients were matched based on underlying nephrotoxicity risk factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
17
2
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 20 publications
1
17
2
1
Order By: Relevance
“…Previous studies that evaluated concomitant vancomycin and piperacillin‐tazobactam found an increased risk of AKI with the combination compared with vancomycin alone or with cefepime . In our study, we found no statistically significant difference in the incidence of AKI between patients given vancomycin in combination with piperacillin‐tazobactam and those given vancomycin with cefepime.…”
Section: Discussioncontrasting
confidence: 71%
See 4 more Smart Citations
“…Previous studies that evaluated concomitant vancomycin and piperacillin‐tazobactam found an increased risk of AKI with the combination compared with vancomycin alone or with cefepime . In our study, we found no statistically significant difference in the incidence of AKI between patients given vancomycin in combination with piperacillin‐tazobactam and those given vancomycin with cefepime.…”
Section: Discussioncontrasting
confidence: 71%
“…Three published studies that evaluated the incidence of AKI with piperacillin‐tazobactam and vancomycin included a subset of patients with critical illness . One study compared two generic vancomycin products for potential differences in nephrotoxicity and used multivariate analysis of overall nephrotoxicity risk factors .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations